Cytotaxonomy of the endemic Karst and Danxia ferns in Adiantum (Pteridaceae) - Wang, Ai-Hua; Yu, Xiao-Ling; Ma, Xiao-Dong; Yan, Yue-Hong; Wang, Fa-Guo; Chen, Hong-Feng (Phytotaxa, 2022)
Chromosome traits may differ between closely related ferns growing in different geological landscapes. Adiantum series Gravesiana (Pteridaceae) includes six species, of which, five species are exclusively distributed in Karst landforms, and one, Adiantum juxtapositum, grows on Danxia landform. Additionally, there are some populations or individuals whose morphology are between different species, which may be the results of polyploidization or hybridization. Here we studied chromosome numbers of species in series Gravesiana primarily using crosiers. Results are: A. longzhouensis and A. juxtapositum were diploids with 2n = 60 and 2n = 64, respectively; A. dentatum was deduced to be diploids with 2n = ca. 60; A. mariesii had two cytotypes, 2n = 60 (diploid) and 2n = ca. 120 (tetraploid), respectively; A. gravesii had four cytotypes including 2n = ca. 60 (diploid), ca. 120 (tetraploid), ca. 150 (pentaploid), and ca. 180 (hexaploid). All these different cytotypes suggest polyploidization and hybridization have occurred in A. gravesii and A. mariesii, so we treated these two species as two “complex group”. All chromosome numbers in this study are the first record.